The Idea of Europe: East and West in Greek Political Philosophy - Kazlauskas, Raimondas (Sociologija. Mintis ir veiksmas, 1999)
The aim of the article is to develop a critique of Europe as a cultural model for political integration. The author takes his departure in an image of Europe of nations, lands, and regions and grounds the critique of the European civilization on a Ancient Greek model of political community. The author raises a question of what is the main principle of civilization: culture or citizenship. He notes the immanent possibility of the culture to become a universal system of values and attempts to define citizenship as the basis of civilization. The author argues that the idea of human as a political being that is found in Greek philosophy from Solon to Aristotle stands in tension with a hierarchicaly organized political forms built around universalistic cultures. Such an argument is built around the interpretation of the ideas of Isocrates, who, drawing on Gorgias and late sophist philosophers, developed a critique of a notion of natural inequality between the Greeks and the Asian barbarians.
Keywords: idea of Europe; greek political philosophy; polis; Isocrates; sophist philosophy; Solon; Aristotle